La Public History tra scuola, università e territorio Una introduzione operativa - Bandini, Gianfranco; Bianchini, Paolo; Borruso, Francesca; Brunelli, Marta; Oliviero, Stefano (Public History of Education. Teorie, esperienze, strumenti, 2022)
The volume collects ten essays, followed by thirty Best Practices sheets, which collectively provide an outline of the interconnections between Public History and schools. Through discussing and hypotheses of teaching and educational paths the essays collected here reflect on the implicit educational value of Public History. The book also opens towards systematic integration with the territory, its publics, and identity traditions, through its interactions with Public History, schools and the university, in relation to other educational institutions and in various local contexts, in particular, school museums. Special attention is devoted to digital experiences and their great contribution to the sharing of historical knowledge.